On the identity of Deliphrum nepalicum Coiffait, 1977 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini) - Shavrin, Alexey V. (Zootaxa, 2018)
Deliphrum nepalicum was described without comparisons by Coiffait (1977) based on a female from “Environs de Maharigaan (Jumla District, eastern Nepal). A study of the holotype and additional material revealed that D. nepalicum undoubtedly belongs to the genus Olophrum Erichson, 1839 (see generic characters in Scheerpeltz (1929), Newton et al. (2000), Zanetti (2012) etc.). Thus, a new combination is proposed: Olophrum nepalicum (Coiffait 1977) comb.n. The species is redescribed, distributional map and ecological data are provided. The aedeagus of O. nepalicum is illustrated for the first time.